2021
DOI: 10.21203/rs.3.rs-576949/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Old Age, Number and Specific Comorbidities are Closely Related to Progression and Poor Prognosis in Patients with COVID-19

Abstract: Background— Some patients with comorbidities and rapid disease progression have a poor prognosis.Aim—In this study, we aimed to investigate the distribution characteristics of comorbidities and their relationship with disease progression and outcomes of COVID-19 patients.Methods— A total of 718 COVID-19 patients were divided into five clinical type groups and eight age-interval groups. The distribution characteristics of comorbidities were compared between the different clinical type groups and between the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Function alteration of specific T lymphocyte subsets (including regulatory T (Treg) cells) results in the hypothesis thatT2D autoimmunity was exacerbated by partial inflammation ( 30 ). Our previous study showed that the lowest lymphocyte counts, especially T and B subsets were found in patients with severe COVID-19 and DM ( 15 18 ). Previous study showed that obese diabetic subjects presented much higher levels of polyclonal activation and antibody secretion in B cell, with impaired ability to response to new antigens such as seasonal influenza vaccination.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Function alteration of specific T lymphocyte subsets (including regulatory T (Treg) cells) results in the hypothesis thatT2D autoimmunity was exacerbated by partial inflammation ( 30 ). Our previous study showed that the lowest lymphocyte counts, especially T and B subsets were found in patients with severe COVID-19 and DM ( 15 18 ). Previous study showed that obese diabetic subjects presented much higher levels of polyclonal activation and antibody secretion in B cell, with impaired ability to response to new antigens such as seasonal influenza vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, specific comorbidities associated with immunodeficiencies (including cancer, CHB, CKD, NAFLD, CVD and DM) often coexist with SARS-CoV-2 infection, which leads to host immune responses dysregulation and thus exacerbating already aggravated inflammatory processes. Patients with COVID-19 are more severe organ damage, more susceptible to bacterial infections and a poor prognosis ( 15 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations